Assessing the Impact of Sago-Themed Environmental Education on Students' Systems Thinking and Critical Thinking Competencies - Abdul Rachman Tiro; Retno Wuri Sulistyowati; Jaharudin Jaharudin; Hafsemi Rapsanjani; Wa Ode Siti Hamsinah Day; Sitti Rahma Yunus (Universitas Syiah Kuala, 2026)
Degradation of sago forest ecosystems in Papua poses a significant threat to regional environmental sustainability and food security. This study aims to evaluate the impact of sago themed environmental education on students’ thinking and critical thinking, which are studied as core dimensions of key competencies for sustainability (KCS). A quasi-experimental method with a one-group pretest-post test design was employed, involving students at Universitas Pendidikan Muhammadiyah Sorong. Data was collected through competency tests validated using the Rasch Model and were analyzed to determine the N-gain scores. It was found that the implementation of sago themed environmental education significantly improved students' sustainability competencies. The results showed a mean N-gain of 0.67, with critical thinking skills achieving the highest improvement at 0.75. Students demonstrated an enhanced ability to analyze complex interconnections within the Sago ecosystem and evaluate revitalization solutions based on scientific data. This study concludes that integrating local wisdom with project-based learning effectively bridges theoretical knowledge and real-world environmental challenges. The program provides a strategic framework for developing the high-level thinking skills necessary to support the achievement of sustainable development goals